The comics of Charles Schulz the good grief of modern life - Gardner, Jared; Gordon, Ian 1954- (University Press of Mississippi, 2017)
"With contributions by: Leonie Brialey, MJ Clarke, Roy T. Cook, Joseph J. Darowski, Ian Gordon, Gene Kannenberg Jr., Christopher P. Lehman, Anne C. McCarthy, Ben Owen, Lara Saguisag, Ben Saunders, Jeffrey O. Segrave, and Michael Tisserand The Comics of Charles Schulz collects new essays on the work of the creator of the immensely popular Peanuts comic strip. Despite Schulz's celebrity, few scholarly books on his work and career have been published. This collection serves as a foundation for future study not only of Charles Schulz (1922-2000) but, more broadly, of the understudied medium of newspaper comics. Schulz's Peanuts ran for a half century, during which time he drew the strip and its characters to express keen observations on postwar American life and culture. As Peanuts' popularity grew, Schulz had opportunities to shape the iconography, style, and philosophy of modern life in ways he never could have imagined when he began the strip in 1950. Edited by leading scholars Jared Gardner and Ian Gordon, this volume ranges over a spectrum of Schulz's accomplishments and influence, touching on everything from cartoon aesthetics to the marketing of global fast food. Philosophy, ethics, and cultural history all come into play. Indeed, the book even highlights Snoopy's global reach as American soft power. As the broad interdisciplinary range of this volume makes clear, Peanuts offers countless possibilities for study and analysis. From many perspectives--including childhood studies, ethnic studies, health and exercise studies, as well as sociology--The Comics of Charles Schulz offers the most comprehensive and diverse study of the most influential cartoonist during the second half of the twentieth century."--
Keywords: Schulz, Charles M. -- 1922-2000 -- Peanuts; USA; Schulz, Charles M. / (Charles Monroe) / 1922-2000 / Criticism and interpretation; Schulz, Charles M. / (Charles Monroe) / 1922-2000 / Peanuts; Peanuts (Comic strip); Comic books, strips, etc / United States / History and criticism; LITERARY CRITICISM / Comics & Graphic Novels; SOCIAL SCIENCE / Popular Culture; HUMOR / Form / Comic Strips & Cartoons; HISTORY / United States / 20th Century; Aufsatzsammlung